2023
DOI: 10.1126/sciadv.add2743
|View full text |Cite
|
Sign up to set email alerts
|

Convergent genomics of longevity in rockfishes highlights the genetics of human life span variation

Abstract: Longevity is a defining, heritable trait that varies dramatically between species. To resolve the genetic regulation of this trait, we have mined genomic variation in rockfishes, which range in longevity from 11 to over 205 years. Multiple shifts in rockfish longevity have occurred independently and in a short evolutionary time frame, thus empowering convergence analyses. Our analyses reveal a common network of genes under convergent evolution, encompassing established aging regulators such as insulin signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 124 publications
0
14
0
Order By: Relevance
“…The top genes identified in their study do not feature in our notes on our top 25 LLL loci though, as all of us do, the authors find a relationship between their loci of interest and p53, in this case via PLA2R1. We note Treaster et al [41] and Kowalczyk et al [15] emphasize insulin signaling pathways, though apparently the particular pathways are under increased constraint in mammals (gene IGF1) but accelerated in Rockfish (gene INSR).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The top genes identified in their study do not feature in our notes on our top 25 LLL loci though, as all of us do, the authors find a relationship between their loci of interest and p53, in this case via PLA2R1. We note Treaster et al [41] and Kowalczyk et al [15] emphasize insulin signaling pathways, though apparently the particular pathways are under increased constraint in mammals (gene IGF1) but accelerated in Rockfish (gene INSR).…”
Section: Discussionmentioning
confidence: 90%
“…A key part of the analysis pipeline was the detection of rate shifts using the TRACCER tool [7]. Unlike Kolora et al [42], and the other studies we mention, Treaster et al [41] treated longevity as a binary trait and argued against the need to correct for body size. The authors found the ancestral rockfish state to be long-lived, and linked positive selection to glycogen biosynthesis and flavonoid metabolism via GO analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations